Smart Cities, Smarter land Use? Unveiling the efficiency gains from China’s digital urban transformation - Zhenyu Zhuo; Jiashuo Ye; Yu Wang; Hao Chen; Bin Liang (Ecological Indicators)
Urban smart transformation serves as a key driver of high-quality economic development in the digital economy era, playing a crucial role in advancing sustainable urban growth. This paper analyzes panel data from 282 prefecture-level cities in China over 12 years, employing the SBM-Undesirable model to measure urban land use efficiency (ULUE). By treating the smart city construction policy as a quasi-natural experiment, this study uses a time-varying DID approach to assess the impact of urban smart transformation on ULUE and employs moderating and spatial effect models to explore underlying mechanisms. The findings reveal that: (1) Smart city construction significantly enhances ULUE, with increases of 16 %, 11.4 %, and 11.1 % of the three pilot batches; (2) Urban smart transformation improves ULUE through three mechanisms: fostering innovation investment, expanding internet user bases, and optimizing industrial land use efficiency; (3) Urban smart transformation has a more pronounced effect on ULUE in eastern and western cities, while the impact in central cities is not significant; (4) The long-term effects of smart city policy surpass short-term impacts and exhibit synergistic interactions with innovation policies; (5) Urban smart transformation has a spatial spillover effect, benefiting neighboring cities within an 80 km radius by significantly boosting ULUE. This paper employs rigorous empirical methods to analyze the causal relationship between urban smart transformation and ULUE, while also delving into the underlying mechanisms, time lag effects, and spatial spillovers. Furthermore, the study offers actionable policy recommendations. These insights provide valuable guidance for sustainable urban development strategies in developing countries.